Using of oxygenic infusion solutions in treatment of patients with bronchial asthma - E. V. Belousov; G. Ts. Dambaev; O. A. Avramchik; E. I. Korotkova; N. I. Belousova; A. E. Kutsenko (Бюллетень сибирской медицины)
Oxygen concentration before and after oxygenation and relaxation time were determined by the method of cathodic voltammetry in infusion solutions, such as physiologic solution — 0.9% NaCl, Ringer-Locc’s solution, glucose — 10%, poliglucin, haemodes, oxigenated by 5 athm. pressure.There were given the recommendations for practical usage of oxigenated infusical solutions.The most optimal solutions for the oxygenotherapy are physiologic solution and poliglucin. 12 patients with bronchial asthma were treated with these solutions successfully.